Tunable Intranasal Polymersome Nanocarriers Triggered Olanzapine Brain Delivery and Improved In Vivo Antipsychotic Activity - Ahmed A. Katamesh; Hend Mohamed Abdel-Bar; Rania Mahafdeh; Mohammed Khaled Bin Break; Shimaa M. Hassoun; Gehad M. Subaiea; Mostafa E. El-Naggar; Khaled Almansour; Hadel A. Abo El-Enin; Heba A Yassin (Pharmaceutics)
Background: Olanzapine (Ola) is a second-generation antipsychotic with clinical utility limited by poor brain bioavailability due to blood–brain barrier restriction, hepatic first-pass metabolism, and systemic side effects. This study aimed to develop and optimize a novel intranasal polymersome-based nanocarrier (PolyOla) to enhance brain targeting, therapeutic efficacy, and safety of Ola. Methods: PolyOla was prepared using poloxamer 401 and optimized through a Box–Behnken Design to minimize particle size and maximize entrapment (EE%) and loading efficiency (LE%). The formulation was characterized by size, morphology, drug release, and serum stability. In vivo studies in adult male Sprague-Dawley rats assessed pharmacokinetics (plasma and brain concentrations), pharmacodynamic efficacy in a ketamine-induced schizophrenia model, and systemic safety markers including metabolic, hepatic, and testicular oxidative stress indicators. Results: Optimized PolyOla exhibited a particle size of 78.3 ± 4.5 nm, high EE% (91.36 ± 3.55%), and sustained in vitro drug release. It remained stable in serum for 24 h. Intranasal administration significantly improved brain delivery of Ola, achieving a 2.7-fold increase in Cmax and a 5.7-fold increase in AUC compared to oral dosing. The brain Tmax was 15 min, with high drug-targeting efficiency (DTE% = 365.38%), confirming efficient nose-to-brain transport. PolyOla-treated rats showed superior antipsychotic performance, reduced extrapyramidal symptoms, and improved systemic safety evidenced by mitigated weight gain, glycemic control, normalized liver enzymes, and reduced oxidative stress. Conclusions: PolyOla offers a safe and effective intranasal delivery platform for Ola, enabling targeted brain delivery and improved management of schizophrenia with reduced peripheral toxicity.